Sustainable tourism development in Bangladesh: Challenges and opportunities to promote the Sundarbans - Uchinlayen Uchinlayen; Bipul Kumar Sarker; Sanjoy Kumar Saha (Goodwood Publishing, 2022)
Purpose: The main objective of this study is to determine what needs to be managed and what obstacles make this World Heritage Site more attractive to tourists through sustainable development. Research Methodology: The study was mainly quantitative in nature. To acquire primary data, the upazilas of Koira and Dumuria in the Khulna district, as well as Shyamnagar, Debhata, and Tala in the Satkhira district, were conveniently sampled because a sizable portion of Sundarbans are located there. A total of 365 individuals from five preselected locations completed a standardized questionnaire to provide information, and respondents were selected using a simple random sampling procedure. Statistics, such as frequency and percentage, and the logistic regression (LR) model were used to examine the data. Results: Among the independent variables included in the NES framework, only eight variables—advantages of natural diversity, natural complications, compatibility, multi-culture opportunity, diversity of life, job opportunity, GDP contribution, and income opportunity—significantly influenced the sustainable development of tourism in the Sundarbans area. Limitations: This research is based on the selected sample about the sustainability, protection, and promotion of Sundarbans, but most of the respondents had limited ideas about these key issues. Contributions: If a sustainable communication system and a standard resort or hotel-motel are built, domestic and foreign tourists will be interested. Additionally, specific policies and adequate security arrangements should be implemented. Above all, the concerned ministries of the government should come forward to create awareness among the people living in the Sundarban area to protect the natural diversity of the region.